Modulation of Host Immune Response Is an Alternative Strategy to Combat SARS-CoV-2 Pathogenesis - Singh, Lakhveer; Bajaj, Sakshi; Gadewar, Manoj; Verma, Nitin; Ansari, Mohd Nazam; Saeedan, Abdulaziz S.; Kaithwas, Gaurav; Singh, Manjari (Frontiers in Immunology, 2021)
The novel SARS-CoV-2virus that caused the disease COVID-19 is currently a pandemic worldwide. The virus requires an alveolar type-2 pneumocyte in the host to initiate its life cycle. The viral S1 spike protein helps in the attachment of the virus on toACE-2 receptors present on type-2 pneumocytes, and the S2 spike protein helps in the fusion of the viral membrane with the host membrane. Fusion of the SARS-CoV-2virus and host membrane is followed by entry of viral RNA into the host cells which is directly translated into the replicase-transcriptase complex (RTC) following viral RNA and structural protein syntheses. As the virus replicates within type-2 pneumocytes, the host immune system is activated and alveolar macrophages start secreting cytokines and chemokines, acting as an inflammatory mediator, and chemotactic neutrophils, monocytes, natural NK cells, and CD8+ T cells initiate the local phagocytosis of infected cells. It is not the virus that kills COVID-19 patients; instead, the aberrant host immune response kills them. Modifying the response from the host immune system could reduce the high mortality due to SARS-CoV-2 infection. The present study examines the viral life cycle intype-2 pneumocytes and resultant host immune response along with possible therapeutic targets.